Tunable Synthesis of N,C-Codoped Ti3+-Enriched Titanium Oxide Support for Highly Durable PEMFC Cathode - Lee, Eungjun; Park, Changmin; Lee, Dong Wook; Lee, Gibaek; Park, Hee-Young; Jang, Jong Hyun; Kim, Hyoung-Juhn; Sung, Yung-Eun; Tak, Yongsug; Yoo, Sung Jong (AMER CHEMICAL SOC, 2020)
The hydrogen economy expansion triggered studies on the durability of hydrogen-powered proton-exchange membrane fuel cells (PEMFCs), which revealed that their performance is largely hindered by the degradation of cathode support. Herein, Ti3+-enriched N,C-codoped mixed-phase TiO2 nanoparticles featuring a reduced (compared to that of pristine TiO2) band gap and containing Ti3+ ions, oxygen vacancies, and Ti-X bonds (X = O, OH, N, C) were synthesized as a durable PEMFC cathode support by annealing. The extent of doping was controlled by adjustment of dopant (urea) loading, while the abundance of defect sites resulted in an enhanced metal-support interaction (i.e., Pt-Ti bonding) for Pt/N,C-codoped TiO2, as confirmed by the shift of the most prominent Pt-0 peak of Pt/N,C-codoped TiO2 to lower binding energies (by 0.96 eV) relative to that of Pt/C. Electrochemical performance testing of the above support revealed its high activity for the oxygen reduction reaction and elevated durability. In particular, a maximum power density decrease of only 4% (cf. 52% for Pt/C under the same conditions) and high durability under PEMFC operation conditions were observed in a single-cell test. Thus, the presented results highlight the great potential of TiO2 as an electrocatalyst support, paving the way to the fabrication of high-performance hydrogen fuel cells and contributing to the establishment of a hydrogen society.